Correlation of simulation/finite element analysis to the separation of intrinsically magnetic spores and red blood cells using a microfluidic magnetic deposition system. Issue 5 (9th February 2018) - Sun, Jianxin; Moore, Lee; Xue, Wei; Kim, James; Zborowski, Maciej; Chalmers, Jeffrey J.
Abstract : Magnetic separation of cells has been, and continues to be, widely used in a variety of applications, ranging from healthcare diagnostics to detection of food contamination. Typically, these technologies require cells labeled with antibody magnetic particle conjugate and a high magnetic energy gradient created in the flow containing the labeled cells (i.e., a column packed with magnetically inducible material), or dense packing of magnetic particles next to the flow cell. Such designs, while creating high magnetic energy gradients, are not amenable to easy, highly detailed, mathematic characterization. Our laboratories have been characterizing and developing analysis and separation technology that can be used on intrinsically magnetic cells or spores which are typically orders of magnitude weaker than typically immunomagnetically labeled cells. One such separation system is magnetic deposition microscopy (MDM) which not only separates cells, but deposits them in specific locations on slides for further microscopic analysis. In this study, the MDM system has been further characterized, using finite element and computational fluid mechanics software, and separation performance predicted, using a model which combines: 1) the distribution of the intrinsic magnetophoretic mobility of the cells (spores); 2) the fluid flow within the separation device; and 3) accurate maps of the values of the magnetic field (max 2.27 T), and magnetic energy gradient (max of 4.41 T 2 /mm) within the system. Guided by this model, experimental studies indicated that greater than 95% of the intrinsically magnetic Bacillus spores can be separated with the MDM system. Further, this model allows analysis of cell trajectories which can assist in the design of higher throughput systems. Abstract : Simulated paths of RBCs of three different magnetophoretic mobilites, mean, one with 1 standard deviation above the mean, and one with 1 standard deviation below the mean, at three different injection locations. Two flow rates were used: 0.5 and 0.1 mls/hr, 9A, 9B, respectively.